2018
DOI: 10.1111/1759-7714.12815
|View full text |Cite
|
Sign up to set email alerts
|

Pretreatment hematological markers predict clinical outcome in cancer patients receiving immune checkpoint inhibitors: A meta‐analysis

Abstract: BackgroundImmune checkpoint inhibitors (ICIs) have revolutionized the clinical treatment of multiple cancers. Recent studies revealed the potential prognostic value of the neutrophil to lymphocyte ratio (NLR) and platelet to lymphocyte ratio (PLR) in patients receiving ICIs; however, the results were inconsistent. We conducted a meta‐analysis to identify the prognostic significance of baseline NLR and PLR in cancer patients treated with ICIs.MethodsWe conducted a thorough literature search of PubMed, Embase, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
32
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(35 citation statements)
references
References 45 publications
3
32
0
Order By: Relevance
“…The dynamics of NLR and ANC during nivolumab treatment may be associated with the efficacy of the subsequent salvage chemotherapy. Many studies have shown that low baseline NLR and ANC predict the efficacy of nivolumab therapy in various cancers . More recent studies have shown that an early decrease in NLR during treatment with PD‐1 inhibitors predicts its efficacy .…”
Section: Discussionmentioning
confidence: 99%
“…The dynamics of NLR and ANC during nivolumab treatment may be associated with the efficacy of the subsequent salvage chemotherapy. Many studies have shown that low baseline NLR and ANC predict the efficacy of nivolumab therapy in various cancers . More recent studies have shown that an early decrease in NLR during treatment with PD‐1 inhibitors predicts its efficacy .…”
Section: Discussionmentioning
confidence: 99%
“…144 A recent meta-analysis of 17 studies showed that a raised pre-treatment NLR was associated with a 1.81 increased risk of progression and 2.26 increased risk of death across malignancies. 145 This could be attributed to neutrophilia/lymphopenia, indicating an intrinsically immune-tolerogenic microenvironment, and leading to inferior response rates and a poorer prognosis. Interestingly, a number of studies have shown a superior predictive ability of post-treatment rather than pre-treatment NLR in correlating with outcome, suggesting systemic inflammation to be a dynamic rather than static predictive correlate of treatment benefit.…”
Section: Molecularly Targeted Modulation Of Cancerrelated Inflammationmentioning
confidence: 99%
“…146,147 While PLR has also been linked to poorer OS and PFS in ICItreated patients, no significant difference was found in the context of the aforementioned meta-analysis, possibly because of the small number of relevant studies available. 145,148,149 Similarly, contradictory results have arisen when evaluating the predictive role of mGPS in the setting of ICI treatment. For instance, one study found that mGPS was superior to NLR and other inflammation-based scores in determining outcomes in NSCLC patients treated with nivolumab, while another study refuted such an association.…”
Section: Molecularly Targeted Modulation Of Cancerrelated Inflammationmentioning
confidence: 99%
See 2 more Smart Citations